Analisis Siklamat Berbagai Merk Kopi Sachet Yang Di Jual Di Pasar Keputih Surabaya - Kartikorini, Nastiti; Ariana, Diah; Samsudin, Rinza Rahmawati; Mardiyah, Siti; Kunsah, Baterun (Indonesian Academia Health Sciences Journal, 2023)
Coffee is a type of plant that contains caffeine and can be processed into a delicious drink. In the process of making coffee usually used artificial sweeteners and natural sweeteners. People prefer artificial (synthetic) sweeteners because they are relatively cheap and easy to obtain. The artificial sweetener that is often used by traders is cyclamate. Cyclamate is highly soluble in water and has a sweetness level of 30 times that of sugar. According to research conducted by Indoforum, 2008 in Sebayang, et.al. 2015, Artificial sweeteners (cyclamate) can have negative effects on human health. This study aims at Cyclamate Analysis of Various Brands of Coffee Sachets Sold at Pasar Keputih Surabaya. This type of research is descriptive with a total sample of 30 samples, with qualitative analysis. Using the deposition reaction test method, namely if there is a white precipitate of BaSO4, it means that the sample contains cyclamate / the sample is positive. The results of the cyclamate analysis study on 30 samples of sachet packaged coffee drinks taken from the Surabaya keputih market were not detected or did not contain cyclamate, this was because no white precipitate of BaSO4 was formed when analyzed with the BaCl2 reaction. It can be concluded that the 30 samples of coffee drinks that were The cyclamate has been examined and does not contain artificial sweeteners (cyclamate).